2001
DOI: 10.1086/318300
|View full text |Cite
|
Sign up to set email alerts
|

The Narrow‐Line Region of Seyfert Galaxies: Narrow‐Line Seyfert 1 Galaxies versus Broad‐Line Seyfert 1 Galaxies

Abstract: It is known that the spectral energy distribution (SED) of the nuclear radiation of narrow-line Seyfert 1 galaxies (NLS1Ïs) has di †erent shapes with respect to that of ordinary broad-line Seyfert 1 galaxies (BLS1Ïs) particularly in X-ray wavelengths. This may cause some di †erences in the ionization degree and the temperature of gas in narrow-line regions (NLRs) between NLS1Ïs and BLS1Ïs This paper aims to examine whether or not there are such di †erences in the physical conditions of NLR gas between them. Fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 74 publications
7
45
0
Order By: Relevance
“…In our spectrum, the Paα line can be separated into a broad and a narrow component with the broad component showing a width of 2081 km s −1 which is typical for a narrow line Seyfert 1 galaxy. This is consistent with the findings of Nagao et al (2001) and Rodríguez-Ardila et al (2000b) who determined the FWHM of Hα to be 1870 km s −1 and classified the object as a narrow line Seyfert 1 galaxy, too. As in HE 1013-1947, the broad component's shape looks slightly asymmetric what could be caused by an unresolved helium-line.…”
Section: He 1029-1831supporting
confidence: 92%
See 1 more Smart Citation
“…In our spectrum, the Paα line can be separated into a broad and a narrow component with the broad component showing a width of 2081 km s −1 which is typical for a narrow line Seyfert 1 galaxy. This is consistent with the findings of Nagao et al (2001) and Rodríguez-Ardila et al (2000b) who determined the FWHM of Hα to be 1870 km s −1 and classified the object as a narrow line Seyfert 1 galaxy, too. As in HE 1013-1947, the broad component's shape looks slightly asymmetric what could be caused by an unresolved helium-line.…”
Section: He 1029-1831supporting
confidence: 92%
“…Nagao et al (2001) as well as Rodríguez-Ardila et al (2000b) find HE 1013-1947 to be a narrow line Seyfert 1 galaxy with a broad component in Hα and Hβ of about 1900 km s −1 , which is narrower than the line width we extracted using Paα.s The difference between the optical and NIR-linewidths could be explained by extinction effects. The slight blueshift of the center of the broad component versus the center of the narrow component could indicate that an unresolved He line (λ1.838 µm) influences our measurement.…”
Section: He 1013-1947mentioning
confidence: 58%
“…If the line width is under estimated by a factor of 2, then the BH mass can be as large as that of a typical radio-loud quasars in the BQS sample. Since this object possesses all properties of an NLS1, it comes to the question of whether the NLS1 phenomena is an orientation effect, i.e., a flat BLR seen face-on (Nagao, Murayama, & Taniguchi 2001) or is due to different physical parameters such as a large L=L Edd (BG92). The radio properties suggest that this object is seen at a small inclination angle, but the picture of a small BH mass and a large accretion rate is also self-consistent.…”
Section: Discussionmentioning
confidence: 99%
“…This is most probably due to the fact that they modelled the broad Balmer component with a Gaussian rather than a Lorentzian. On the other hand, Nagao et al (2001) showed that the line ratios [ …”
Section: The Line Ratios Of the Narrow Line Regionmentioning
confidence: 99%